Conflitos parentais nos processos de regulação do exercício das responsabilidades parentais e a atuação do processo de promoção e proteção - Cruz, Neuza Rafaela Meira (2021)
The parental conflict has been the first major problem identified in Family and Children jurisdiction cases, namely on those regarding the regulation of the exercise of Parental Responsibilities, in the event of a family breakdown. Excessive and on-going parental conflicts, such as behaviours to manipulate the child and create disaffection towards the other parent, the enormous lack of communication between parents and, sometimes, even harsher situations, such as domestic violence, will always be against the best interests of the child. These behaviours affect the child safety and emotional balance severely, leading to situation “of danger” within the meaning of Article 3(2)(f) of the Portuguese Law for the Protection of Children and Youngsters in Danger. Being the parental conflict identified as a hazardous situation, the need for a protective intervention in this family home emerges, due to the Government role in protecting children through opening a proceeding of Promotion and Protection. Once the proceedings of Promotion and Protection are initiated, it is fundamental to connect this proceeding to the one concernig a regulation of the exercise of parental responsibilities; and subsequently, verify which action, in terms of promotion and protection, is adequate to the situation. This protective action will aim at, essentially, to raise the parent’s awareness of their parental duties. Nonetheless, in a domestic violence situation, since it involves more complex matters, this intervention will focus on other aspects. For a better comprehension of the harmonisation between the referred proceedings, as well as the protective intervention needed in the parental conflicts, it is required to go through the evolution of the implementation of children’s rights over the years as well as the creation of legal instruments to guarantee their effectiveness.